Analysis of free and forced convections in the flow of radiative viscous fluid with oxytactic microorganisms - Bilal, S.; Ullah, Asad; Shah, Imtiaz Ali; Asjad, Muhammad Imran; Almusawa, Musawa Yahya; Eldin, Sayed M. (Frontiers in Materials, 2023)
The prime intend behind the current effort is to explicate flow attributes of magnetically influenced Newtonian fluids toward a stretchable sheet under the novel physical impact of oxytactic microorganisms in a comparative manner for free and forced convections. In addition, modified Fourier and Fick’s laws are implemented to examine the change in temperature and concentration distributions in a more realistic manner by accounting thermal and mass relaxation parameters in the flow. The obtained PDEs are reduced into the non-linear ODEs by employing similarity variables. Due to the complexity of parametrically based differential equations, a numerical scheme based on a finite-difference approach is implemented via the MATLAB built-in routine known as BVP4C. Flow-controlling parameter effects on associated distributions are evaluated through graphs and tables. Subsequently, the influence of flow-controlling parameters on associated distributions is revealed through pictures in a comparative manner for different convection regimes. Additionally, the quantities such as heat and mass fluxes along with the density of motile microorganisms are also illustrated. From the thorough analysis of the current investigation, it is inferred that velocity distribution enhances for free and forced convections, whereas the temperature of the fluid diminishes against the mentioned convective regimes. It is manifested that the Nusselt number is more in the situation of free convection instead of the forced convection situation. The magnitude of the skin friction factor is more in case of free convection as compared to the forced convection regime. It is also reported that by uplifting the magnitudes of concentration and thermal relaxation parameters, depreciation in associated heat and mass transfer rate arises. In addition, it is also reported that with the increment in the magnetic field, buoyancy ratio, bioconvection parameters, and Rayleigh number skin friction accelerate, while the behavior is quite opposite in case of stretching the ratio parameter.